Rapid Bacterial Detection during Endodontic Treatment. (June 2017) - Herzog, D.B.; Hosny, N.A.; Niazi, S.A.; Koller, G.; Cook, R.J.; Foschi, F.; Watson, T.F.; Mannocci, F.; Festy, F.
Bacteria present in the root canal (RC) space following an RC treatment (RCT) can lead to persistent infections, resulting in treatment failure and the need for reintervention or extraction. Currently, there are no standardized methods in use to clinically detect bacterial presence within RC spaces. The use of paper point sampling and fluorescence staining was shown to be a rapid method, able to detect residual bacteria following treatment. The study demonstrated that Calcein acetoxymethyl (AM) proved to be a suitable dye for detecting vital bacteria within mature endodontic biofilms, with an improved sensitivity over colony-forming unit counting in a stressed biofilm model. Furthermore, in a clinical trial with primary RCTs, 53 infected teeth were sampled in vivo, and increased detection of vital cells was found when compared with colony-forming unit counting, highlighting the sensitivity of the technique in detecting low cell numbers. By combining fluorescent staining and microspectroscopy with software-based spectral analysis, successful detection of vital cells from RCs was possible after 5 min of Calcein AM incubation. Application of this technology during RCT has the potential to reduce persistent infections through vital cell detection and additional treatment. Furthermore, this technique could be applied to antimicrobial research and disinfection control in clinical settings (ClinicalTrials.gov NCT03055975).